Descartes' Error: Emotion, Reason and the Human Brain - Hurtubise, Rolland (Relations industrielles / Industrial Relations, 1995)
The article reviews the book, "Descartes' Error: Emotion, Reason and the Human Brain," by Antonio R. Damasio.
Keywords: Book reviews; Brain; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Emotions; Labor Unions; Logic; Reason; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z